Enhanced binding by dextran‐grafting to Protein A affinity chromatographic media. Issue 7 (15th March 2017) - Zhao, Lan; Zhu, Kai; Huang, Yongdong; Li, Qiang; Li, Xiunan; Zhang, Rongyue; Su, Zhiguo; Wang, Qibao; Ma, Guanghui
Abstract : Dextran‐grafted Protein A affinity chromatographic medium was prepared by grafting dextran to agarose‐based matrix, followed by epoxy‐activation and Protein A coupling site‐directed to sulfhydryl groups of cysteine molecules. An enhancement of both the binding performance and the stability was achieved for this dextran‐grafted Protein A chromatographic medium. Its dynamic binding capacity was 61 mg immunoglobulin G/mL suction‐dried gel, increased by 24% compared with that of the non‐grafted medium. The binding capacity of dextran‐grafted medium decreased about 7% after 40 cleaning‐in‐place cycles, much lower than that of the non‐grafted medium as decreased about 15%. Confocal laser scanning microscopy results showed that immunoglobulin G was bound to both the outside and the inside of dextran‐grafted medium faster than that of non‐grafted one. Atomic force microscopy showed that this dextran‐grafted Protein A medium had much rougher surface with a vertical coordinate range of ±80 nm, while that of non‐grafted one was ±10 nm. Grafted dextran provided a more stereo surface morphology and immunoglobulin G molecules were more easily to be bound. This high‐performance dextran‐grafted Protein A affinity chromatographic medium has promising applications in large‐scale antibody purification.